(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current situation and some factors related to reporting adverse drug reactions (ADR) at Nghe An General Friendship Hospital in 2023. Research methods: Cross-sectional descriptive study with evaluation conducted on 130 reports of adverse drug reactions and 27 medical staff at Nghe An General Friendship Hospital from October 2023 to April 2024. Research results: ADR reports with complete information accounted for 96.2%, mainly by nurses (70.3%). The average age of patients is 52.62 ± 21.65, the majority are in the age range of 18-60 (50.8%); The male/female ratio is 0.9. Infectious and parasitic diseases have the highest rate (34.38%), followed by respiratory system diseases (15.63%). There were 46 active ingredients/135 active ingredients with recorded ADRs, of which Vancomycin, Amoxicillin/Clavulanic Acid and Ceftizoxim were the most recorded active ingredients (13.28%, 9.38% and 9.38%). Skin reactions account for the highest rate (44.3%); Some general manifestations and respiratory disorders were 14.9%, 14.5%, respectively. Manifestations on the skin and mucous membranes include: itching (20.6%); rash (13.6%); red skin, flushing (10.3%). Mild and moderate ADR manifestations account for the highest proportion (67.2%). The reason for not reporting an ADR shared by medical staff is that they are overloaded with work and do not have time to report (51.9%). Most medical staff have no difficulty reporting ADRs (48.1%). However, difficulty identifying the suspected drug (33.3%), lack of time (22.2%), and difficulty determining the severity of the ADR (18.5%) are also main obstacles. The main proposed measure is to promote coordination between doctors, pharmacists and nurses to support ADR reporting (63%). Conclusion: ADRs causing skin reactions account for the highest rate (44.3%); Some general manifestations and respiratory disorders were 14.9% and 14.5%, respectively. Vancomycin causes ADR with the highest rate of allergy, erythema, difficulty breathing, and chest pain (10.94%), while Amoxicillin/Clavulanic Acid causes allergy and low blood pressure (8.59%).